Multidisciplinary Approach to the Diagnosis and In-Hospital Management of COVID-19 Infection: A Narrative Review - Lo Bianco, Giuliano; Di Pietro, Santi; Mazzuca, Emilia; Imburgia, Aurelio; Tarantino, Luca; Accurso, Giuseppe; Benenati, Vincenzo; Vernuccio, Federica; Bucolo, Claudio; Salomone, Salvatore; Riolo, Marianna (Frontiers in Pharmacology, 2020)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2 or COVID-19 disease) was declared a pandemic on 11th March 2020 by the World Health Organization. This unprecedented circumstance has challenged hospitals’ response capacity, requiring significant structural and organizational changes to cope with the surge in healthcare demand and to minimize in-hospital risk of transmission. As our knowledge advances, we now understand that COVID-19 is a multi-systemic disease rather than a mere respiratory tract infection, therefore requiring holistic care and expertise from various medical specialties. In fact, the clinical spectrum of presentation ranges from respiratory complaints to gastrointestinal, cardiac or neurological symptoms. In addition, COVID-19 pandemic has created a global burden of mental illness that affects the general population as well as healthcare practitioners. The aim of this manuscript is to provide a comprehensive and multidisciplinary insight into the complexity of this disease, reviewing current scientific evidence on COVID-19 management and treatment across several medical specialties involved in the in-hospital care of these patients.